Expanding Distribution, Taxonomy and Morphological Descriptions of the Collected Fish Species Halieutaea indica Annandale & Jenkins, 1910 (Indian Handfish) from the Jafrabad Fish Landing Center, Arabian Sea, Northwest Coast of India - Jungi D. N.; Borichangar R. V.; Jungi P. N.; Parmar J. N.; Tandel B. K.; Tandel S. K. (Archives of Current Research International, 2025)
This study documents the taxonomy and morphology of Halieutaea indica specimens collected from the Gujarat coast, of India. Two specimens (total lengths: 7.6 cm and 10.3 cm) were obtained from a trawler operating from the Jafrabad Fish Landing Center and identified using original species descriptions. A distinguishing feature of seven inverted rostral spines protecting the mouth was observed. Fresh specimens exhibited yellow pectoral fins with a white band near the tip, further corroborating diagnostic characters. Morphometric parameters, including body proportions, fin lengths, and meristic counts, were measured and compared with existing data from earlier studies. The results align with prior morphological descriptions of H. indica, reinforcing its identification and confirming its presence in Gujarat’s coastal waters. This study contributes to baseline data on the species distribution in the Arabian Sea and supports regional biodiversity documentation in understudied fisheries ecosystems.